2021
DOI: 10.1073/pnas.2002557117
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear trends in abundance and diversity and complex responses to climate change in Arctic arthropods

Abstract: Time series data on arthropod populations are critical for understanding the magnitude, direction, and drivers of change. However, most arthropod monitoring programs are short-lived and restricted in taxonomic resolution. Monitoring data from the Arctic are especially underrepresented, yet critical to uncovering and understanding some of the earliest biological responses to rapid environmental change. Clear imprints of climate on the behavior and life history of some Arctic arthropods have been demonstrated, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 72 publications
2
52
0
Order By: Relevance
“…In recent years, many studies have reported declines in insect richness [1][2][3][4][5][6][7]. Nevertheless, it is difficult to generalize trends since regional, taxa-and ecosystem-specific patterns exist [8][9][10][11][12][13]. Although terrestrial insects appear to be declining in many areas, aquatic insects have more frequently been reported to be increasing [14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have reported declines in insect richness [1][2][3][4][5][6][7]. Nevertheless, it is difficult to generalize trends since regional, taxa-and ecosystem-specific patterns exist [8][9][10][11][12][13]. Although terrestrial insects appear to be declining in many areas, aquatic insects have more frequently been reported to be increasing [14].…”
Section: Introductionmentioning
confidence: 99%
“…While climate change has resulted in decreased abundance and diversity for many species (IPCC, 2014 ; Wagner et al, 2021 ), some insect species have increased their population sizes or range due to warmer temperatures. Thus, the damage by insect herbivores is growing, especially at higher elevations and latitudes (Høye et al, 2021 ; Jepsen et al, 2008 , 2011 ). For example, Barrio et al, ( 2017 ) found that 1.4% of leaf area of the circumpolar dwarf birch ( Betula glandulosa ‐ nana complex) is currently lost due to background insect herbivory, and that with a 1°C increase in summer temperatures, insect herbivory will likely increase by 6–7%.…”
Section: Introductionmentioning
confidence: 99%
“…Phenological advancements in arthropod emergence have nevertheless been shown in some time series (Høye et al, 2007; Rakhimberdiev et al, 2018, but see Meltofte et al, 2021) and predicted from climatic dependencies (Shaftel et al, 2021; Tulp & Schekkerman, 2008). How such advancements impact food available for shorebird chicks will also depend on climate‐induced changes in arthropod community composition (Høye et al, 2021; Koltz et al, 2018), body size (Tseng et al, 2018) activity (Høye & Forchhammer, 2008), and variation in abundance outside of the peak (Machín et al, 2018; Saalfeld et al, 2019). Therefore, whether the occurrence of trophic mismatches is increasing for Arctic‐nesting shorebirds is currently unclear.…”
Section: Discussionmentioning
confidence: 99%